The returns to education and the wage effect from overeducation in Trinidad and Tobago: A pseudo-panel approach - Doon, Roshnie; Scicchitano, Sergio (Global Labor Organization (GLO), Essen, 2024)
Having highly educated workers can be beneficial for organizations in terms of innovation and problem-solving capabilities, however when underpaid and underemployed, overeducated workers may experience feelings of frustration and stagnation as they are unable to fully utilize their skills and knowledge. This can result in high levels of job dissatisfaction and a high employee turnover rate. While the literature on returns to education and overeducation is extensive in developed countries, evidence from developing (and Caribbean) countries remains scarce. This study will aim to examine the returns to education and the overeducation of public sector workers in Trinidad and Tobago. By using the Ordinary Least Squares (OLS), Quantile Regression (QR), Recentred Influence Function (RIF) and a pseudo-panel approach to address the presence of Omitted Variable Bias (OMV), and Endogeneity, as well as CSSP data for 1991-2015, this study finds that the average returns to education in Trinidad and Tobago are 19.2% highlighting the downward bias from the OLS estimate of 11.5%. The average returns of overeducated workers although positive appear to be influenced by their year of birth, so the earnings of overeducated persons born between 1935-1942, and 19431950, were lower than workers born later on in 1975-1982, and 1983-1990.
Keywords: Education Mismatch; Overeducation; Quantile Regression; Recentred Influence Function; Pseudo Panel; Public Sector